Birth and Neonatal Outcomes Following Opioid Use in Pregnancy: A Danish Population-Based Study - Nørgaard, Mette (Subst Abuse, 2015)
BACKGROUND: Few population-based data exist on birth outcomes in women who received opioid maintenance treatment during pregnancy. We therefore examined adverse birth outcomes in women exposed to methadone or buprenorphine during pregnancy and the risk of neonatal abstinence syndrome (NAS) among neonates exposed to buprenorphine, methadone, and/or heroin in utero. PATIENTS AND METHODS: This study included all female Danish residents with a live birth or a stillbirth from 1997 to 2011. We identified the study population, use of opioids and opioid substitution treatment, birth outcomes, and NAS through medical registers. Birth outcomes included preterm birth (born before 38th gestational week), low-birth weight (LBW) (<2,500 g, restricted to term births), small for gestational age (SGA) (weight <2 standard deviations from the sex- and gestational-week-specific mean), congenital malformations, and stillbirths. We used log-binomial regression to estimate the prevalence ratio (PR) for birth outcomes. RESULTS: Among 950,172 pregnancies in a total of 571,823 women, we identified 557 pregnancies exposed to buprenorphine, methadone, and/or heroin (167 to buprenorphine, 197 to methadone, 28 to self-reported heroin, and 165 to combinations). Compared with nonexposed pregnancies, prenatal opioid use was associated with greater prevalence of preterm birth (PR of 2.8 (95% confidence interval (CI), 2.3–3.4)), LBW among infants born at term (PR of 4.3 (95% CI, 3.0–6.1)), and being SGA (PR of 2.7 (95% CI, 1.9–4.3)). Restricting the analyses to women who smoked slightly lowered these estimates. The prevalence of congenital malformations was 8.3% in opioid-exposed women compared with 4.2% in nonexposed women (PR of 2.0 (95% CI, 1.5–2.6)). The risk of NAS ranged from 7% in neonates exposed to buprenorphine only to 55% in neonates exposed to methadone only or to opioid combinations. CONCLUSION: The maternal use of buprenorphine and methadone during pregnancy was associated with increased prevalence of adverse birth outcomes, and this increase could only be explained to a smaller extent by increased prevalence of smoking. The risk of NAS was eight-fold higher in methadone-exposed neonates than that in buprenorphine-exposed neonates, but this difference may at least partly be explained by differences in underlying indications (analgesic versus opioid maintenance treatment) between the two groups.